Resilience in mothers of children with cerebral palsy. Cienfuegos. 2018 - Yianet Molina Rodríguez; María Felicia Casanova González; Anais Marta Valladares González; Misleydis D´Escoubet Cuesta (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Foundation: the family is the main link in stimulating their children, especially mothers, the first significant figure in the child's emotional life. Then, they will need adequate preparation to be resilient when facing the alterations of the neuro-development of their children, especially those who have suffered cerebral palsy. Objective: To describe the level of resilience and its modulating factors in mothers whose children suffer from cerebral palsy. Methods: descriptive cross-sectional study, supported methodologically in the research mixed approach, conducted at Paquito González Cueto University Pediatric Hospital, from September 2017 to March 2018. It included 24 mothers of children with cerebral palsy, from the municipality of Cienfuegos, who attended the Provincial Consultation of Early Assistance. The variables were analyzed: age, type of relationship, school level, occupation, resilience capacity, self-esteem level, optimism and emotional intelligence. Results: the most represented age group was from 26 to 35 years old (58.33%), consensual union was presented in 54.17%; predominantly pre-university school level (50%), housewives (54.17%); desired pregnancy was more representative (91.67%), as well as the low capacity of resilience with 66.66%, average level of self-esteem (50%); optimism was absent in 70.83% and low emotional intelligence in 58.33%. Conclusions: mothers studied had low resilience and modulating factors with a medium level of self-esteem, lack of optimism, and low levels of emotional intelligence.